ADOPSI INOVASI BUDIDAYA MANGROVE DI PULAU UNTUNG JAWA KEPULAUAN SERIBU - Diarsi Eka Yani (University of Jember, 2014)
This research is aimed to analyze (1) the characteristics of the mangrove farmers at Untung Jawa island, Seribu archipelago, and (2) characteristics of the innovations. This study used a survey method for data collection. The study population was a whole group of farmers who cultivated mangrove at Untung Jawa island, Seribu archipelago. Samples taken was 15 people by a simple random method. Data collected consisted of primary and secondary data which were analyzed by descriptive statistics to identity the performance characteristics of farmers mangrove communities at Untung Jawa island and the characteristics of the innovations. The characteristics of the community members involved in this study include (1) age, (2) education, (3) motivation, (4) family income, (5) the courage to take risk, (6) the level of participation in the group/organization, (7) activity on searching information and new ideas. Meanwhile, innovation characteristics include (1) relative advantage, (2) compatibility, (3) complexity, (4) trialability, and (5) observability. The results indicated that respondents who cultivate mangrove were mostly categorized as young, having primary school education, having a short period of farming, motivated to increase revenue, having the lowest income levels, having the courage to take risk, getting the information from the instructor or group leader. For the characteristics of the innovations, most respondents said that the application of cultivation of mangrove has enough profit to add their insights and income, in accordance with the requirements of innovation and the needs of the growing plants, innovation mangrove planting technique is not difficult, it is simple and easy to learn by all respondents, cultivating innovation easy to try, and innovation mangrove cultivation is easy to be observed. Keyword: characteristics, innovation, mangrove cultivation, seribu archipelago